Editoras políticas no Porto, anos 1960-1970 : da oposição à ditadura ao pós-25 de Abril - Flamarion Maués (História - Revista da Faculdade de Letras da Universidade do Porto, 2014)

(untitled)
Some publishing houses in Portugal had a notable political role from the end of the 1960s to the late 1970s. They published books that clearly opposed Salazar’s regime, and after the Revolution of April 25th they kept publishing works that greatly contributed to the political debate in the country. At least 24 of these political publishing houses were located in the city of Oporto, although their distribution and influence could reach the whole of Portugal. In this paper I present a general outline of these publishing houses and analyze in detail some of them. To conclude, I indicate which publishing houses were more important in the Portuguese political process both before and after the Carnation Revolution, pointing out some specificity of Oporto political publishing features.